Using Seasonal Climate Variability Forecasts: Risk Management for Tomato Production in South Florida - Norman Breuer; Phyllis Gilreath; Gene McAvoy; David Letson; Clyde Fraisse (EDIS)
This paper is divided into three main sections. The first part briefly describes the difference between weather and climate. The second section suggests some management options available to tomato growers with regards to seasonal climate forecasts. The third part discusses economic and risk management implications of seasonal climate variability for tomato producers and extensionists looking at a broader context in South Florida. This document is Circular 1450, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Sciences, University of Florida. First published June 2004.